The Curse of Wealth - Middle Eastern Countries Need to Address the Rapidly Rising Burden of Diabetes - Lisa Klautzer; Joachim Becker; Soeren Mattke (Kerman University of Medical Sciences, 2014)
The energy boom of the last decade has led to rapidly increasing wealth in the Middle East, particularly in the oil and gas-rich Gulf Cooperation Council (GCC) countries. This exceptional growth in prosperity has brought with it rapid changes in lifestyles that have resulted in a significant rise in chronic disease. In particular the number of people diagnosed with diabetes has increased dramatically and health system capacity has not kept pace. In this article, we summarize the current literature to illustrate the magnitude of the problem, its causes and its impact on health and point to options how to address it.